2014
DOI: 10.1021/ac502897g
|View full text |Cite
|
Sign up to set email alerts
|

Depth Profiling of Element Concentrations in Stratified Materials by Confocal Microbeam X-ray Fluorescence Spectrometry with Polychromatic Excitation

Abstract: The confocal microbeam X-ray fluorescence technique is a well-established analytical tool that is widely used for qualitative and quantitative analysis of stratified materials. There are several different reconstruction methods dedicated to this type of samples. However, these methods are applicable with monochromatic excitation only. The full description of matrix effects and geometrical effects for polychromatic X-ray photons in confocal geometry is a demanding task. In the present paper, this problem was ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The spectral distribution of the primary radiation emitted from the X-ray tube, filtered by the polycapillary optics, was calculated by the scheme presented in Wrobel et al [29] Herein, the effective energy of~10 keV was found. *the boundary water fractions in the brain structures studied are in italics …”
Section: Spectral Analysismentioning
confidence: 99%
“…The spectral distribution of the primary radiation emitted from the X-ray tube, filtered by the polycapillary optics, was calculated by the scheme presented in Wrobel et al [29] Herein, the effective energy of~10 keV was found. *the boundary water fractions in the brain structures studied are in italics …”
Section: Spectral Analysismentioning
confidence: 99%
“…Sequential series of confocal XRF measurements along lines and planes allows to visualize the distribution of chemical elements of interest in one or two dimensions, creating, for example, virtual depth profiles, and two-or three-dimensional distributions inside the materials of interest [23,100,101]. After its original introduction at synchrotron radiation facilities [97,[101][102][103][104][105], the feasibility of performing confocal XRF measurements using tube sources was demonstrated by several groups around the world [106][107][108][109][110], along with appropriate deconvolution, quantification, and simulation models [111][112][113][114][115][116][117][118]. Several papers have been recently been published where confocal XRF measurements are exploited for sub-surface examination of painted works of art [119][120][121][122][123][124], next to pottery [125], coins [86], stained glass [126,127], painted metal sheet [128], and natural rock samples [129].…”
Section: _####_ Page 6 Of 51mentioning
confidence: 99%
“…Cordes et al 413 reported the use of laboratory-based X-ray techniques for the non-destructive elemental quantication of polymerembedded thin lms. Wrobel et al 415 performed depth proling of element concentrations in stratied materials by confocal m-XRF spectrometry with polychromatic excitation. Confocal m-XRF and nano-CT were successfully coupled for these measurements in order to meet these sensitivity and spatial resolution specications necessary for characterising thin lms.…”
Section: Thin Lms Coatings and Nanomaterialsmentioning
confidence: 99%
“…Multilayered paint fragments of a car were analysed non-destructively to demonstrate that this confocal m-XRF instrument could be used in the discrimination of the various layers in multilayer paint systems. Wrobel et al 415 performed depth proling of element concentrations in stratied materials by confocal m-XRF spectrometry with polychromatic excitation. The authors extended a method, well established for monochromatic radiation, to polychromatic radiation by effective energy approximation.…”
Section: Thin Lms Coatings and Nanomaterialsmentioning
confidence: 99%